Comparison of Modified Chandler, Roller Pump, and Ball Valve Circulation Models for In Vitro Testing in High Blood Flow Conditions: Application in Thrombogenicity Testing of Different Materials for Vascular Applications - Wim van Oeveren; Ignace F. Tielliu; Jurgen de Hart (International Journal of Biomaterials)
Three different models, a modified Chandler loop, roller pump, and a new ball valve model (Hemobile), were compared with regard to intrinsic damage of blood components and activation of platelets. The Hemobile was used for testing of polymer tubes. High flow was not possible with the Chandler loop. The roller pump and the Hemobile could be adjusted to high flow, but he pump induced hemolysis. Platelet numbers were reduced in the roller pump and Chandler loop (P<0.05), but remained high in the Hemobile. Platelet aggregation was reduced in all models. The Hemobile was applied for testing vascular graft materials, and allowed different circuits circulated simultaneously at 37°C. ePTFE, Dyneema Purity UHMWPE fiber and PET fiber based tubes, all showed hemolysis below 0.2% and reduced platelet count and function. Binding of fibrin and platelets was higer on PET, inflammatory markers were lowest on Dyneema Purity UHMWPE. We concluded that the Hemobile minimally affects blood and could be adjusted to high blood flows, simulating arterial shear stress. The Hemobile was used to measure hemocompatibility of graft material and showed Dyneema Purity UHMWPE fiber in many ways more hemocompatible than ePTFE and PET.